32Pi Labeled Transgenic Wheat Shows the Accumulation of Phosphatidylinositol 4,5-bisphosphate and Phosphatidic Acid Under Heat and Osmotic Stress - Annum, Nazish; Ahmed, Moddassir; Imtiaz, Khadija; Mansoor, Shahid; Tester, Mark; Saeed, Nasir A. (Frontiers in Plant Science, 2022)
The ensuing heat stress drastically affects wheat plant growth and development, consequently compromising its grain yield. There are many thermoregulatory processes/mechanisms mediated by ion channels, lipids, and lipid-modifying enzymes that occur in the plasma membrane and the chloroplast. With the onset of abiotic or biotic stresses, phosphoinositide-specific phospholipase C (PI-PLC), as a signaling enzyme, hydrolyzes phosphatidylinositol 4,5-bisphosphate (PIP2) to generate inositol 1,4,5-trisphosphate (IP3) and diacylglycerol (DAG) which is further phosphorylated into phosphatidic acid (PA) as a secondary messenger and is involved in multiple processes. In the current study, a phospholipase C (PLC) signaling pathway was investigated in spring wheat (Triticum aestivum L.) and evaluated its four AtPLC5 overexpressed (OE)/transgenic lines under heat and osmotic stresses through 32Pi radioactive labeling. Naturally, the wheat harbors only a small amount of PIP2. However, with the sudden increase in temperature (40°C), PIP2 levels start to rise within 7.5 min in a time-dependent manner in wild-type (Wt) wheat. While the Phosphatidic acid (PA) level also elevated up to 1.6-fold upon exposing wild-type wheat to heat stress (40°C). However, at the anthesis stage, a significant increase of ∼4.5-folds in PIP2 level was observed within 30 min at 40°C in AtPLC5 over-expressed wheat lines. Significant differences in PIP2 level were observed in Wt and AtPLC5-OE lines when treated with 1200 mM sorbitol solution. It is assumed that the phenomenon might be a result of the activation of PLC/DGK pathways. Together, these results indicate that heat stress and osmotic stress activate several lipid responses in wild-type and transgenic wheat and can explain heat and osmotic stress tolerance in the wheat plant.